Description of a new species from Clarias maclareni and phylogenetical analysis of Quadriacanthus (Monogenea, Dactylogyridae) species transfers between clariid and non-clariid fish hosts in Cameroon - Bahanak Dieu-Ne-Dort; Mbondo Jonathan A.; Bassock Bayiha Etienne D.; Pariselle Antoine; Nack Jacques; Bilong Bilong Charles F.; Agnèse Jean-Francois (Parasite, 2022)
Recently in Cameroon, two species belonging to Quadriacanthus: Q. anaspidoglanii Akoumba, Tombi & Bilong Bilong, 2017 and Q. euzeti Nack, Pariselle & Bilong Bilong, 2016 have been recorded on gill filaments of Notoglanidium macrostoma (Siluriformes, Claroteidae) in the Memou’ou River (Nyong Basin) and Papyrocranus afer (Osteoglossiformes, Notopteridae) in Lake Ossa, respectively. These records have been considered the result of lateral transfers from Clariidae to a Claroteidae host for the first case (parasitism of N. macrostoma by Q. anaspidoglanii) and from Clariidae or Bagridae to a Notopteridae host for the second (parasitism of P. afer by Q. euzeti). In this paper, the investigation of interspecific relationships among Quadriacanthus spp. parasitizing Clariidae, Bagridae, Claroteidae and Notopteridae in Cameroon resulted in the record of Q. anaspidoglanii from N. macrostoma, Q. euzeti from P. afer, a new record of Q. levequei Birgi, 1988 from Clarias jaensis in the Nyong River, and the description of Q. barombiensis n. sp. from Clarias maclareni in Lake Barombi Mbo. The newly identified species is characterized by having an accessory piece ending in one small hook and the median expansion of its dorsal bar with two filaments. Phylogenetic analysis based on 28S rDNA sequences confirms that the Quadriacanthus spp. parasitizing gill filaments of non-clariid hosts in Cameroon originate from lateral transfers from clariid fishes, and that Clariidae are ancestral hosts of these monogenean species.